Fabrication of 6FDA-durene membrane incorporated with zeolite T and aminosilane grafted zeolite T for CO2/CH4 separation - Jusoh, N. (Institute of Physics Publishing, 2017)
In the present work, zeolite T and aminosilane grafted zeolite T are embedded into 6FDA-durene polyimide phase for the fabrication of mixed matrix membranes (MMMs). FESEM images demonstrated that the improvement of interfacial adhesion between zeolite and polymer phases in MMM loaded with aminosilane grafted zeolite T was not significant as compared to zeolite T/6FDA-durene MMM. From the gas permeation test, CO2/CH4 selectivity up to 26.4 was achieved using MMM containing aminosilane grafted zeolite T, while MMM loaded with ungrafted zeolite T showed CO2/CH4 selectivity of 19.1. In addition, MMM incorporated with aminosilane grafted zeolite T particles successfully lies on Robeson upper bound 2008, which makes it an attractive candidate for CO2/CH4 separation. © Published under licence by IOP Publishing Ltd.